Multiple Genomic Regions Govern Tolerance to Sulfentrazone in Snap Bean (Phaseolus Vulgaris L.) - Saballos, Ana; Soler-Garzón, Alvaro; Brooks, Matthew; Hart, John Patrick; Lipka, Alexander Edward; Miklas, Philip; Peachey, Ronald Edward; Tranel, Patrick J.; Williams, Martin M. (Frontiers in Agronomy, 2022)
The availability of effective weed management tools against waterhemp (Amaranthus tuberculatus) is crucial to maintain profitable production of snap bean (Phaseolus vulgaris L.). Preemergence herbicides enable the crop to gain a size advantage over the weed, but the few preemergence herbicides registered in snap bean have poor control of waterhemp. Sulfentrazone, a protoporphyrinogen oxidase (PPO) -inhibiting herbicide, provides significant control of waterhemp and other problematic weeds. However, crop tolerance to the herbicide is poorly known. To quantify snap bean tolerance to sulfentrazone and investigate the underlying tolerance mechanism(s), a genome-wide association mapping study was conducted using field-collected data on a snap bean diversity panel. Response to a preemergence application of sulfentrazone was measured using plant population density and shoot biomass variables. High levels of crop tolerance were found in several entries including Bush Romano 71, Navarro, and Flamata. Snap bean tolerance to sulfentrazone is associated with multiple genomic regions, indicating the trait is likely non-target site resistance (NTSR) mediated. Seed size is partially responsible for the tolerance, thus the genetic factors conditioning sulfentrazone tolerance are likely a combination of those driven indirectly by seed size/weight and those acting directly on the metabolism of the herbicide or ameliorating its damage. In this study, several cytochrome P450 and ABC transporter genes were localized in associated genomic regions. Alleles conditioning snap bean tolerance to sulfentrazone identified in the diversity panel shed light on herbicide metabolism and could be used in snap bean improvement.